A New Six-DoF Parallel Mechanism for Captive Model Test - Lu Yun; Wu Jinbo; Li Weijia; Wu Yaozhong (Polish Maritime Research, 2020)
In order to obtain the hydrodynamic coefficients that can save cost and meet the accuracy requirements, a new hydrodynamic test platform based on a 6DoF (six degrees of freedom) parallel mechanism is proposed in this paper. The test platform can drive the ship to move in six degrees of freedom. By using this experimental platform, the corresponding hydrodynamic coefficients can be measured. Firstly, the structure of the new device is introduced. The working principle of the model is deduced based on the mathematical model. Then the hydrodynamic coefficients of a test ship model of a KELC tank ship with a scale of 1:150 are measured and 8 typical hydrodynamic coefficients are obtained. Finally, the measured data are compared with the value of a real ship. The deviation is less than 10% which meets the technical requirements of the practical project. The efficiency of measuring the hydrodynamic coefficients of physical models of ships and offshore structures is improved by the device. The method of measuring the hydrodynamic coefficients by using the proposed platform provides a certain reference for predicting the hydrodynamic performance of ships and offshore structures.